Crystal Facet and Architecture Engineering of Metal Oxide Nanonetwork Anodes for High-Performance Potassium Ion Batteries and Hybrid Capacitors - Chang, Chao-Hung; Chen, Kuan-Ting; Hsieh, Yi-Yen; Chang, Che-Bin; Tuan, Hsing-Yu (ACS nano, 2022)
Metal oxides are considered as prospective dual-functional anode candidates for potassium ion batteries (PIBs) and hybrid capacitors (PIHCs) because of their abundance and high theoretic gravimetric capacity; however, due to the inherent insulating property of wide band gaps and deficient ion-transport kinetics, metal oxide anodes exhibit poor K electrochemical performance. In this work, we report crystal facet and architecture engineering of metal oxides to achieve significantly enhanced K storage performance. A bismuth antimonate (BiSbO ) nanonetwork with an architecture of perpendicularly crossed single crystal nanorods of majorly exposed (001) planes are synthesized CTAB-mediated growth. (001) is found to be the preferential surface diffusion path for superior adsorption and K transport, and in addition, the interconnected nanorods gives rise to a robust matrix to enhance electrical conductivity and ion transport, as well as buffering dramatic volume change during insertion/extraction of K . Thanks to the synergistic effect of facet and structural engineering of BiSbO electrodes, a stable dual conversion-alloying mechanism based on reversible six-electron transfer per formula unit of ternary metal oxides is realized, proceeding by reversible coexistence of potassium peroxide conversion reactions (KO ↔K O) and Bi Sb alloying reactions (BiSb ↔ KBiSb ↔ K BiSb). As a result, BiSbO nanonetwork anodes show outstanding potassium ion storage in terms of capacity, cycling life, and rate capability. Finally, the implementation of a BiSbO nanonetwork anode in the full cell configuration of both PIBs and PIHCs shows satisfactory performance in a Ragone plot that sheds light on their practical applications for a wide range of K -based energy storage devices. We believe this study will propose a promising avenue to design advanced hierarchical nanostructures of ternary or binary conversion-type materials for PIBs, PIHCs, or even for extensive energy storage.